2007
DOI: 10.1073/pnas.0709876105
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond electron tunneling between the hemes in cytochrome bo 3

Abstract: Biological electron transfer (eT) between redox-active cofactors is thought to occur by quantum-mechanical tunneling. However, in many cases the observed rate is limited by other reactions coupled to eT, such as proton transfer, conformational changes, or catalytic chemistry at an active site. A prominent example of this phenomenon is the eT between the heme groups of mitochondrial cytochrome c oxidase, which has been reported to take place in several different time domains. The question of whether pure eT tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
45
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 51 publications
(71 reference statements)
6
45
1
Order By: Relevance
“…The heme iron separations differ in the two proteins by less than 0.5 Å, and the nearby methyl groups distances differ by 0.8 Å, based on the x-ray structures [differences well within the range of thermal fluctuations (19)]; the coupling pathway structure is nearly the same in the two proteins, involving the bonded His-Phe-His path linking irons and the direct methyl-tomethyl through-space contact. Taking a minimum donor-acceptor distance of 7.8 Å, a (generic) packing density value (2,14), and a typical ET reorganization energy (0.7 eV) places rates computed with packing analysis in agreement with experimental rates (20). However, recent studies have found a reorganization energy for cytochrome bo 3 of Ͻ0.2 eV, so the kinetics cannot be accommodated with the packing density reported by Dutton and coworkers (20).…”
Section: Coupling Routes and Tunneling Barriers In Cytochrome C Oxidasementioning
confidence: 67%
See 4 more Smart Citations
“…The heme iron separations differ in the two proteins by less than 0.5 Å, and the nearby methyl groups distances differ by 0.8 Å, based on the x-ray structures [differences well within the range of thermal fluctuations (19)]; the coupling pathway structure is nearly the same in the two proteins, involving the bonded His-Phe-His path linking irons and the direct methyl-tomethyl through-space contact. Taking a minimum donor-acceptor distance of 7.8 Å, a (generic) packing density value (2,14), and a typical ET reorganization energy (0.7 eV) places rates computed with packing analysis in agreement with experimental rates (20). However, recent studies have found a reorganization energy for cytochrome bo 3 of Ͻ0.2 eV, so the kinetics cannot be accommodated with the packing density reported by Dutton and coworkers (20).…”
Section: Coupling Routes and Tunneling Barriers In Cytochrome C Oxidasementioning
confidence: 67%
“…Moreover, small changes in the model parameters or medium sampling rules will shift atoms in or out of the packing density analysis. Jasaitis et al (2) point to the ''large local variation of the packing density'' in the space between the hemes, meaning that the computed density is model dependent. Dominant single pathways are particularly likely to arise at short ET distances, so it is not surprising that difficulties with ''coarsegrained'' models occur for the cytochrome bo 3 and cytochrome c oxidase heme-to-heme reactions.…”
Section: Coupling Routes and Tunneling Barriers In Cytochrome C Oxidasementioning
confidence: 99%
See 3 more Smart Citations